An assessment of current practices on landslides risk management: a case of Kuala Lumpur territory - Anas Alnaimat,; Lam, Kuok Choy; Mokhtar Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In Kuala Lumpur to date, there is little evidence to support landslide causes and very little research into the nature of landslide vulnerability. This article takes an interdisciplinary method and empirical approaches to examine, in addition where necessary, challenge a series of assumptions made regarding Landslide Risk Management (LRM) with a view to developing better understanding of social vulnerability on landslide hazard and its underlying causes alongside combine expert judgment on triggering factors. Moreover, the contribution of Malaysia Public Works Department (PWD/JKR) via the implication of National Slope Master Plan (NSMP 2009-2023) operational capabilities and its effectiveness on landslide risk mitigation measures is reviewed. The finding on the influence of landslide causative and triggering factors have shown steepness of slope was greatly functioned as a landslide primary causative factor on mass movement whereas, in Kuala Lumpur rainfall and human activities plays significant role in triggering landslide on a slope vulnerable to failure. The result suggests occupants of landslide prone areas have decent perceptions of landslide and its associated risk. Contrary wise, a loss of confidence by local residents on government authorities on implementing appropriate hazard mitigation measures, lack of voluntary data sharing and insufficiency public awareness campaigns conducted by Malaysian local authorities.